Program Promosi Kesehatan “Food Smart Campus: Jadi Mahasiswa Sehat” - Yuwanda, Muhammad Fajar (Lembaga Yasin AlSys, 2025)
This study is motivated by the limited research on improving healthy eating habits among university students through behavior modification approaches, despite the significant impact of diet on physical and mental health, particularly for final-year students. The aim of this research is to evaluate the effectiveness of a healthy eating education intervention based on the token economy system in improving students’ understanding and behavior regarding healthy eating. A quantitative method with a one-group pretest-posttest experimental design was used. The sample consisted of four final-year students selected through simple random sampling. Data were collected using a questionnaire developed based on the